Assessing customer-capturing strategies considering network effects and multiple adoption. (1st January 2014) - Tseng, Fan-Chen; Teng, Ching-I
Network effects offer competitive advantages for market leaders in the information technology industry. Although various strategies for new challengers to gain market share have been proposed, the tendency of users to adopt multiple technologies simultaneously has not been studied. This study thus presents a novel concept – user preference for the market-leading technology. The effectiveness of customer-capturing strategies proposed by Teng et al. (2006) is reassessed. The results of this study demonstrate that when considering multiple adoption, user preference for market-leading technology correlates negatively with effectiveness of a challenger's customer-capturing strategies, which goes beyond the findings of Teng et al. (2006).